PROSES PERUMUSAN KEBIJAKAN SERTIFIKASI PENDIDIK : Suatu Penelitian tentang Proses Formulasi Kebijakan Sertifikasi Pendidik Bagi Guru Dalam Jabatan sebagai Tenaga Profesional - Wibowo, Udik Budi (2010)
Educator certification policy initially has relatively low acceptability and implementability as demonstrated by controversions and fidgetiness to teacher community. The problem was supposed caused by formulation process of certification policy inappropriate to principality and regulation. So, this research gets to know the profile of formulation process of certification policy. This study is retrospective policy research, or backward mapping research by qualitative approach. Data collecting worked by review of documents and elite interviewing or specialized interviewing, with purposive sample based-on snowball or referent sampling, including parliament (legislative), government (executive), and teacher association (PGRI). The research had the use of interpretative inductive analysis. The research find that formulation process of certification policy utilize legal rational model with prominent value preference is teachers welfare increasing. The problems and controversies happened because the initial policy target is teacher candidates, not on-the-job teachers; indolence of policy formulation process; political-will to allocate certification budget, inconsistencies between operational rule to welfare increasing princip, and incomprehensive consideration on resources and anticipate consequences and policy risks. Based on the research findings, it's recommended to Government to well regulate in formulate educational policies, and School Principal and Education Board in order that evolving an empowering mechanism of certified teachers. Then, to advance research, it's recommended to study on the effect of teacher certification policy to education quality, and the influence of political power in the educational policy formulation. Key words: Policy formulation, educator sertification, on-the-job teachers, professional.